Peran Instagram dalam Pemasaran Alat Kecantikan pada Akun @MISSGLAM_ID - Nadhila, Saradiva; Jamil, Khoirul (Lembaga penelitian dan pengabdian kepada Masyarakat, 2024)
Social media causes changes in the marketing context, especially in terms of promotion that makes the creation of online businesses. Instagram is one of the most popular social media. Instagram is a social media that helps businesses market products online. This research focuses on Miss Glam, a beauty shop that sells a variety of beauty products and uses Instagram as a means of communication in marketing products. The purpose of this study is to determine the role of Instagram in marketing beauty tools on the @missglam_id account. This research uses the AIDA theory, which can be used to examine how Instagram plays a role in marketing. This research uses qualitative methods with data collection techniques in the form of interviews and journal literature reviews. The results of this study, based on informants from 5 people (1 admin of the @missglam_id Instagram account and 4 followers account), show that the role of Instagram in marketing beauty products on the @missglam_id account is very effective, both in terms of Instagram features and interaction with followers.